2022
DOI: 10.1177/00131245221076095
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Principals’ Distributed Leadership Behaviors on Teachers’ Attitudes Toward Multiculturalism: Social Justice Leadership as Mediator

Abstract: With the increasing cross-country immigration and human mobility, different cultures are reflected more in the schools. The behavioral patterns of educational leaders in multicultural settings and the affecting factors have been subject to many discussions and researches. This study examines the relationship between school principals’ distributed leadership behaviors and teachers’ social justice leadership and attitudes toward multiculturalism. A structural model has been created and tested through the mention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 115 publications
0
5
0
1
Order By: Relevance
“…For example, Torres (2018) found that in Singapore principals' distributed leadership had a significant positive association with teachers' job satisfaction. Sonmez and Gokmenoglu (2023) found that in Turkey principals' distributed leadership behaviors had a positive effect on cultivating teachers' supporting attitudes toward multiculturalism. These studies suggest that principals' distributed leadership has an important influence on teachers' cognitions and beliefs.…”
Section: Distributed Leadership and Teachers' Motivationmentioning
confidence: 95%
“…For example, Torres (2018) found that in Singapore principals' distributed leadership had a significant positive association with teachers' job satisfaction. Sonmez and Gokmenoglu (2023) found that in Turkey principals' distributed leadership behaviors had a positive effect on cultivating teachers' supporting attitudes toward multiculturalism. These studies suggest that principals' distributed leadership has an important influence on teachers' cognitions and beliefs.…”
Section: Distributed Leadership and Teachers' Motivationmentioning
confidence: 95%
“…The entire architecture of a marginalised person's thinking will potentially have been conditioned by their structural context: leadership will in part be a reprogramming job before any new vision can be installed. A deconstruction of the social justice leader's own cognitive biases is an essential prerequisite (Sonmez & Gokmenoglu, 2022). As a major pillar of the traditional Orang Asli identity is a specific way of knowing the world, SJL cannot afford to ignore it.…”
Section: Sjl In the Orang Asli Contextmentioning
confidence: 99%
“…Kepimpinan distributif yang berkesan berupaya memupuk komitmen guru. Kepimpinan distributif merupakan satu pasukan pemimpin berinteraksi antara satu sama lain dan bekerjasama mengikut kemahiran pengikut demi memajukan organisasi (Sonmez & Gokmenoglu, 2022). Lantaran itu, Kementerian Pendidikan Malaysia (KPM) melalui anjakan ke-5 Pelan Pembangunan Pendidikan Malaysia (PPPM) 2013-2025 telah beralih ke arah model kepimpinan distributif untuk memupuk gaya kepimpinan yang lebih berkesan untuk menjamin setiap sekolah di Malaysia mempunyai pemimpin yang berkualiti.…”
Section: Pengenalanunclassified